2020
DOI: 10.1080/0376835x.2020.1838260
|View full text |Cite
|
Sign up to set email alerts
|

Development visions, livelihood realities – how conservation shapes agricultural value chains in the Zambezi region, Namibia

Abstract: In the Zambezi region, seemingly unrelated political visions propagate two development paths: nature conservation to promote tourism and Community-Based Natural Resource Management (CBNRM), and agricultural intensification. This study examines the unintended interrelations between these top-down visions by linking upgrading possibilities in agricultural value chains (AVC) with livelihood strategies of farmers from a bottomup perspective. The results are based on qualitative field research that explains the how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…First, its economy is mainly based on two sectors: agriculture and tourism (Hulke, Kairu, and Revilla Diez 2020). Although economic activities such as timber export, fishing, and logistics exist on a limited scale, the region is traditionally characterized by small-scale crop farming and cattle herding for subsistence use (Mendelsohn 2006).…”
Section: Case Study and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, its economy is mainly based on two sectors: agriculture and tourism (Hulke, Kairu, and Revilla Diez 2020). Although economic activities such as timber export, fishing, and logistics exist on a limited scale, the region is traditionally characterized by small-scale crop farming and cattle herding for subsistence use (Mendelsohn 2006).…”
Section: Case Study and Methodsmentioning
confidence: 99%
“…Medium and large-scale irrigation schemes, so-called Green Schemes, ought to realize this vision by including smallholders as outgrowers. However, so far only one Green Scheme has been established in the Zambezi region, which employed six permanent farmers in 2019 (Hulke, Kairu, and Revilla Diez 2020).…”
Section: Case Study and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, protected areas were established across communal lands with a strict zoning plan defining which landuse is allowed and affects e.g. farmers in their daily practices and thus livelihood strategies (Hulke et al 2020). In all cases, political aspirations are meant to create opportunity spaces for the locals.…”
Section: Aspirations As Visions For Developmentmentioning
confidence: 99%
“…Today, 54% of the Zambezi region is protected to varying degrees, including national parks, communal conservancies, a state forest, tourism priority areas and wildlife corridors (own calculation). Continuing a strong critique of earlier conservation approaches, these policies are not undisputed: research has revealed discontent among smallholder farmers regarding harvest losses caused by wildlife, residents claim the distribution of conservancy income does not reach individual households and that the designation of areas for tourist activities negatively affects agriculture (Hulke et al 2020).…”
Section: Accessing a Resource Frontier: Corridor Development And Nature Conservation In The Zambezi Regionmentioning
confidence: 99%